Participant Satisfaction with a Hormonal Intrauterine Device (IUD) Counseling Video - Guijosa, Linda (My University, 2023)
INTRODUCTION: The purpose of this study was to conduct a secondary analysis on hormonal IUD participant feedback data to assess the feasibility of implementing an anticipatory counseling video on a large scale to reach diverse audiences. This analysis also informs future versions of the video for patients representing diverse sociodemographic groups.OBJECTIVES: The primary objectives of this study include: 1. Examine differences between demographic groups based on counseling video ratings; 2. Summarize qualitative feedback on the video; and 3. Provide recommendations for improving the video based on participant feedback. METHODS: This secondary analysis is based on data from a randomized 1:1, double-blinded, placebo controlled online randomized trial conducted at the University of Washington. Both qualitative and quantitative approaches utilizing Microsoft Excel were used to analyze quantitative demographic data and qualitative IUD anticipatory counseling video feedback from the intervention group only (N=94). Qualitative data from the study questionnaire was coded to compare themes among participants from three locations to explore anticipatory counseling video recommendations using a transcendental phenomenology approach. RESULTS: Participants had a generally favorable opinion of the components and quality of the video. They also had some recommendations to make improvements for future versions of this video. Overall, the study participants liked the visual diagrams and the ease of understanding of the video, and the least liked component was the length of the video. DISCUSSION: Given that participants mostly liked the video and felt it had educational value, clinics that offer counseling and insertion of IUDs should consider implementing anticipatory guidance videos to help their patients understand what to expect the first few months when using this contraceptive method.
Thesis (Master's)--University of Washington, 2023
Keywords: anticipatory counseling video; hormonal intrauterine device; reproductive health; women's health; Public health; Health services